Evaluación técnico-financiera del diseño de un fluido de alta tixotropía formulado con sistema de Mezcla de Óxidos de Metal (MMO) para la perforación de la sección reservorio en el campo Castilla a partir de pruebas de laboratorio (2018)
This project began describing the generalities and geology of Campo Castilla, it is necessary to know its history of production and cases associated with the loss of circulation due to natural fractures. The use of a high-thixotropy drilling fluid type MMO (MMO, Mixed-Metal Oxide) is proposed in order to mitigate the generated costs, the system is described with its characteristics and benefits . It started with the choice of the bentonite to be used, since the efficiency of the system depends on the quality of the bentonite, verifying its nature as untreated, as well as the bentonite-MMO ratio that was varied in a relation of 10: 1. The Drill In type fluid was previously formulated by the company Q'Max Solutions, its properties and operational characteristics were compared to highlight benefits. It was finalized with a financial analysis of the two operative scenarios with which the viability of the study was concluded.